Komparasi Metode Peramalan Grey dan Grey-Markov untuk mengetahui Peramalan PNBP di Universitas Udayana - Manuaba, I Dewa Nyoman Anom; Manuaba, Ida Bagus Gede; Sudarma, Made (Majalah Ilmiah Teknologi Elektro, 2022)
Forecasting is the process of estimating a future value using data from the past or data from the present as a reference. Forecasting is a critical component of an organization's short- and long-term planning as a reference for management decision making. Identifying the data pattern in the time series data utilized is a crucial step in identifying the best forecasting approach for the data pattern. The Gray Prediction Model is a forecasting technique that can be used with partial data or a little amount of data. The Grey-Markov forecasting approach may be used to make very accurate forecasts using Udayana University education acceptance data, which is limited, with only five historical data and data patterns classed as horizontal data patterns with modest fluctuations.